A systematic review of instruments measuring grief after perinatal loss and factors associated with grief reactions. Issue 2 (April 2021) - Setubal, M.S.; Bolibio, R.; Jesus, R.C.; Benute, G.G.; Gibelli, M.A.; Bertolassi, N.; Barbosa, T.; Gomes, A.; Figueiredo, F.; Ferreira, R.; Francisco, R.; Stein Bernardes, L.
Abstract: Objective: Expectant parents who live through perinatal loss experience intense grief, which is not always acknowledged or accepted. A screening tool to detect bereaved parents' grief reactions can guide professionals, including perinatal palliative care teams, to provide follow-up for those in need. This review's goal is to identify and synthesize the international published literature on existent instruments specifically measuring the grieving process after any perinatal loss and to identify factors that could moderate grief reactions. Method: Systematic review (PROSPERO # CRD42018092555) with critical synthesis. PUBMED, Cochrane, and PsycINFO databases were searched in English language articles using the keywords "perinatal" AND ("grief" OR "bereavement" OR mourning) AND ("scale" OR "questionnaire" OR "measure" OR "assessment") up to May 2018. Eligibility criteria included every study using a measure to assess perinatal grief after all kinds of perinatal losses, including validations and translations to other languages and interventions designed to alleviate grief symptoms. Results: A total of 67 papers met inclusion criteria. Seven instruments measuring perinatal grief published between 1984 and 2002 are described. The Perinatal Grief Scale (PGS) was used in 53 of the selected studies. Of those, 39 analyzed factors associated with grief reactions. Six articles used PGS scores to evaluate pre- and post-bereavement interventions. Studies in English language only might have limited the number of articles. Significance of results: The PGS is the most used standardized measures to assess grief after perinatal loss. All parents living through any kind of perinatal loss should be screened.